Control of biofouling by xanthine oxidase on seawater reverse osmosis membranes from a desalination plant: enzyme production and screening of bacterial isolates from the full‐scale plant. (1st July 2017) - Nagaraj, V.; Skillman, L.; Li, D.; Xie, Z.; Ho, G.
Abstract: Control of biofouling on seawater reverse osmosis (SWRO) membranes is a major challenge as treatments can be expensive, damage the membrane material and often biocides do not remove the polymers in which bacteria are embedded. Biological control has been largely ignored for biofouling control. The objective of this study was to demonstrate the effectiveness of xanthine oxidase enzyme against complex fouling communities and then identify naturally occurring bacterial strains that produce the free radical generating enzyme. Initially, 64 bacterial strains were isolated from different locations of the Perth Seawater Desalination Plant. In our preceding study, 25/64 isolates were selected from the culture collection as models for biofouling studies, based on their prevalence in comparison to the genomic bacterial community. In this study, screening of these model strains was performed using a nitroblue tetrazolium assay in the presence of hypoxanthine as substrate. Enzyme activity was measured by absorbance. Nine of 25 strains tested positive for xanthine oxidase production, of which Exiguobacterium from sand filters and Microbacterium from RO membranes exhibited significant levels of enzyme production. Other genera that produced xanthine oxidase were Marinomonas, Pseudomonas, Bacillus, Pseudoalteromonas and Staphylococcus . Strain variations were observed between members of the genera Microbacterium and Bacillus . Significance and Impact of the Study: Xanthine oxidase, an oxidoreductase enzyme that generates reactive oxygen species, is endogenously produced by many bacterial species. In this study, production of the enzyme by bacterial isolates from a full‐scale desalination plant was investigated for potential use as biological control of membrane fouling in seawater desalination. We have previously demonstrated that free radicals generated by a commercially available xanthine oxidase in the presence of a hypoxanthine substrate, effectively dispersed biofilm polysaccharides on industrially fouled membranes. Bacterial xanthine oxidase production in the presence of hypoxanthine may prove to be a cost effective, in situ method for alleviation of fouling.